A new species of Antigius (Lepidoptera: Lycaenidae: Theclini) from Taiwan - Hsu, Yu-Feng (Zootaxa, 2009)
Antigius jinpingi, new species, is described from Taiwan, which Theclini fauna has been investigated extensively. The sister species of the new taxon is presumed to be A. butleri, a species distributed in the Asiatic continent and Japan. The larval host plant of A. jinpingi is unknown, but the most likely candidate is Quercus dentata, a deciduous oak with a relictual distribution in Taiwan.